The role of sleep on physical and cognitive performance of ultra-endurance athletes: A systematic review - Guilherme, L. Q.; Rodrigues, B. O.; de Oliveira Barbosa Rosa, C.; Leite, L. B.; Scheer, V.; Forte, P.; Hermsdorff, H. H. M.; Kravchychyn, A. C. P.; de Sá Souza, H. (Journal of Clinical Medicine, 2026)
Background/Objectives: Sleep is an important factor for recovery and performance in endurance sports, yet its role in ultra-endurance events remains unclear due to extreme physical and cognitive demands and disrupted sleep patterns. This systematic review aimed to analyze the role of sleep in physical and cognitive performance in ultra-endurance athletes.